DESCRIPTION OF KNOWLEDGE LEVELS ABOUT DRUG ABUSE IN THE MEDICAL STUDENTS 2019 UNIVERSITAS MALIKUSSALEH - Z, Khairunnisa; Surya Akbar, Teuku Ilhami (Fakultas Kedokteran Universitas Malikussaleh, 2020)
Drug abuse is a world problem that can never be resolved. Nevertheless, efforts towards enforcement and eradication must still be carried out. The difficulty is that the problem created by humans themselves, involves many aspects, including economic, political and moral. Drug use outside the medical indication, without a doctor's prescription or prescription, and use that is pathological (causing abnormalities) can cause obstacles in activities at home, school or campus, workplace and social environment. The purpose of this study was to determine the level of knowledge of drug abuse in the medical students 2019 Universitas Malikussaleh. This research was an descriptif study with cross sectional method. The sample in this study were all students of the medical students 2019 Universitas malikussaleh totaling 96 people. From this study 86% of students had good knowledge of drug abuse and 14% were lacking knowledge.